2017
DOI: 10.1063/1.4982821
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of homogeneous crystal nucleation of the NiAl intermetallic by a composition gradient: A molecular dynamics study

Abstract: Molecular dynamics simulations of homogeneous nucleation of the NiAl intermetallic phase from a liquid solution on cooling indicate that this phase transformation is suppressed in the presence of a composition gradient. A simulation method is designed to generate a sustaining composition gradient at the interface between two materials. As the composition gradient increases, the nucleation energy barrier rises, the critical nucleus size increases, and the nucleus shape develops an increasing asymmetry. A polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This enlightens us that the formation of the critical nucleation of β-CL-20 may be closely related to the cooperativity effect stemming from the noncovalent interactions in the molecular cluster, 102 as has been confirmed by our recent investigation 103 for TNT, a far simpler and smaller explosive molecule in comparison with CL-20. 11 Unfortunately, for a CL-20 molecular cluster containing 20∼30 molecules, the calculation of the high-level intermolecular interactions with the polarization and dispersion basis set is beyond our capacity with our current computing resources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enlightens us that the formation of the critical nucleation of β-CL-20 may be closely related to the cooperativity effect stemming from the noncovalent interactions in the molecular cluster, 102 as has been confirmed by our recent investigation 103 for TNT, a far simpler and smaller explosive molecule in comparison with CL-20. 11 Unfortunately, for a CL-20 molecular cluster containing 20∼30 molecules, the calculation of the high-level intermolecular interactions with the polarization and dispersion basis set is beyond our capacity with our current computing resources.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphism of molecular crystals is a common phenomenon where a system with certain molecular components could be stacked into different crystal lattices with different physical and chemical properties. [1][2][3][4][5][6][7] Understanding the mechanism of polymorphic transformation at the molecular level is of great importance for revealing the essence of the structure-property relationship for polymorphs, 8,9 and providing microscopic dynamics 10 and thermodynamics information in the transformation process, 11 so as to optimize the technological process and obtain the desired polymorph in a wide range of fields such as pharmaceuticals, 12 nonlinear optical materials, 13 energy storage, 14 energetic materials, 15 life substances, 16 etc. However, although the polymorphic transformation of molecular crystals has received significant attention experimentally [5][6][7]10,17,18 and theoretically [19][20][21] for a long time, it still remains extremely difficult to explain how the molecules deviate from the original positions and orientations of the crystal form to aggregate and organize into those of the new form.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that voids and porosity led to a slower mechanism compared to the case in which the two elements were in direct contact. The Weihs group has indirectly studied (vi) in the case of temperature driven mixing [23][24][25] . They noted that a pre-mixing step hindered diffusion and that a nano-scale gradient suppressed the homogeneous nucleation of B2-NiAl.…”
Section: Studied Milled Powders Of Ni+al By Means Of High-resolution Transmission Electronmentioning
confidence: 99%